(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the works of Amiri and Khorezm artists to a certain extent. Information is provided about the scope of the work of Amiri, the founder of the Kokand literary environment, the style of expression. Observations are made about the attitude of representatives of the Khorezm literary environment to the topics addressed by Amiri.